2016
DOI: 10.4103/0970-9185.168149
|View full text |Cite
|
Sign up to set email alerts
|

Role of ketamine for analgesia in adults and children

Abstract: Ketamine an N-methyl-D-aspartate (NMDA) receptor blocking agent and a dissociative anesthetic with neurostimulatory side effects. In recent years, multiple research trials as well as systematic reviews and meta-analyses suggest the usefulness of ketamine as a strong analgesic used in subanesthetic intravenous doses, and also as a sedative. In addition, ketamine was noted to possess properties of anti-tolerance, anti-hyperalgesia and anti-allodynia most likely secondary to inhibition of the NMDA receptors. Tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…It is abused for its ability to produce dissociative sensations and hallucinations. These effects are invariably associated with relatively high dose of ketamine, which might involve interaction with other neurotransmitter systems including the opioid, cholinergic, dopaminergic, and adenosine receptors as well as inflammatory cytokines [ 15 , 16 , 17 ]. Recently, it has become evident that subanesthetic doses of ketamine can have a rapid and long lasting antidepressant effect in various animal models [ 18 ] as well as in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…It is abused for its ability to produce dissociative sensations and hallucinations. These effects are invariably associated with relatively high dose of ketamine, which might involve interaction with other neurotransmitter systems including the opioid, cholinergic, dopaminergic, and adenosine receptors as well as inflammatory cytokines [ 15 , 16 , 17 ]. Recently, it has become evident that subanesthetic doses of ketamine can have a rapid and long lasting antidepressant effect in various animal models [ 18 ] as well as in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from their recreational use, PCP and ketamine have medical applications that include analgesia and anesthesia (Jouguelet-Lacoste, et al, 2015; Nalini et al, 2016; White and Ryan, 1996). Ketamine produces fewer dissociative effects than PCP and the effects are shorter lived, allowing for broader clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Trujillo and Akil ( 1991 ) provided an initial evidence that NMDA antagonists may inhibit the development of morphine tolerance, thus allow prolonged administration of opioid-based analgesics. Since then, numerous studies confirmed this theory in experimental and clinical setting (Bilsky et al, 1996 ; Mao, 1999 ; Bisaga and Popik, 2000 ; Mendez and Trujillo, 2008 ; Lin et al, 2010 ; Vadivelu et al, 2016 ) and synergistic effects between opioids and NMDA antagonists towards pain relief has been demonstrated in several pain models (Nishiyama, 2000 ; Chow et al, 2004 ; Hama and Sagen, 2014 ). This approach has proven to be effective for combination of low-dose ketamine with opioids such as morphine, that showed more effective analgesic effect for pre or postoperative pain with minimal or no side effects.…”
Section: Discussionmentioning
confidence: 86%